PENGARUH JUMLAH WAJIB PAJAK, KEPATUHAN WAJIB PAJAK, DAN PEMERIKSAAN PAJAK TERHADAP PENERIMAAN PAJAK PENGHASILAN BADANPADAKANTOR PELAYANAN PAJAK PRATAMA TEGAL (Students' Journal of Accounting and Banking, 2013)
This study aims to identify and analyze the effect of the number of taxpayers, tax compliance and tax audit of the corporate income tax receipts in KPP Pratama Tegal.This study uses quantitative data using secondary data obtained from KPP Pratama Tegal.The sample used in this study is on the period January 2010 to December 2012. Analysis of the data used in this study is the use of multiple linear regression analysis. The results of this study stated that amount of taxpayers shows a negative significant effect , tax compliance that positive significant effect, and also negative no significant effect of the tax assessment against corporate income tax revenue KPP Pratama Tegal.Keywords: Amount of Taxpayer, Taxpayer Compliance, Tax Audit, Corporate Tax Receipts